2021
DOI: 10.3389/fimmu.2021.772450
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence of Chemotherapy and Toripalimab Might Influence the Efficacy of Neoadjuvant Chemoimmunotherapy in Locally Advanced Esophageal Squamous Cell Cancer—A Phase II Study

Abstract: BackgroundThere is no standard neoadjuvant therapy for locally advanced esophageal cancer in China. The role of neoadjuvant chemotherapy plus immunotherapy for locally advanced esophageal cancer is still being explored.MethodsThis open-label, randomized phase II study was conducted at a single center between July 2019 and September 2020; 30 patients with locally advanced esophageal squamous cell carcinoma (ESCC) (T3, T4, or lymph-node positive) were enrolled. Patients were randomized according to the enrollmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 32 publications
1
59
0
Order By: Relevance
“…Recently, more and more studies revealed that nICT is safe and feasible for patients with LA-ESCC. 8–10 The results demonstrated that nICT had manageable adverse effects, high R0 resection rate, promising pCR rate and limited postoperative complications.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, more and more studies revealed that nICT is safe and feasible for patients with LA-ESCC. 8–10 The results demonstrated that nICT had manageable adverse effects, high R0 resection rate, promising pCR rate and limited postoperative complications.…”
Section: Discussionmentioning
confidence: 87%
“…Among the 27 studies, 8 trials with 221 patients examined nICRT ( 14 21 ), 19 trials with 588 patients examined nICT ( 22 40 ). Except one two-arms trial ( 33 ), all included studies were single-arm trials. Most of trials were conducted in China (20/27).…”
Section: Resultsmentioning
confidence: 99%
“…Most of trials were conducted in China (20/27). ICI was concurrently administered with CT or CRT in all studies except one trial ( 33 ). The most commonly CT regimen was paclitaxel plus carboplatin or cisplatin (PC/TP) (18/27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the structure of EUS, a miniature high-frequency ultrasonic probe is installed on the top of the endoscope, and an ultrasonic scan can be performed by the endoscope entering the body to obtain the ultrasonic images of the features of gastrointestinal tissue. The obtained images can be of some help to more intuitive and accurate diagnosis of disease and the implementation of follow-up targeted treatment plans (28,29). EUS can measure the diameter and cross-sectional area of the esophageal wall and the gastric wall by ultrasound.…”
Section: Introductionmentioning
confidence: 99%